Antibacterial hydrogels for managing wound infections - Yeo, Chun Kiat (Nanyang Technological University, 2020)
Bacterial infection on wounds delay wound healing, and may even deteriorate the wound condition. Diabetic wound healing is even more problematic as patients suffer multiple conditions that prevent wounds from healing. Traditional dressings such as bandage, gauze or plasters are protective rather than proactive. Current antibacterial treatments are typically prophylactic and involve cytotoxic silver, and yet they do not remove bacterial debris. FDA-approved treatments for diabetic wounds also contain contraindications which limit their effectiveness. We have developed novel hydrogels to treat different types of wounds. First, a biocompatible, biofilm-debriding hydrogel was made by UV irradiation of poly(ethylene glycol) dimethacrylate and star cationic polyethylenimine (PEI). It is able to achieve more than 99.9% killing of wound biofilms such as methicillin-resistant Staphylococcus aureus (MRSA), and carbapenem-resistant Pseudomonas aeruginosa (CR-PA) and Acinetobacter baumannii (CR-AB) in a murine excisional wound infection model. Silver-based wound dressings (controls) showed almost no killing of MRSA and CR-PA biofilms. This debridement effect is largely due to the high water swellability and microporosity of the hydrogel, which harnesses hydrodynamic drag of the hydrogel and draws bacteria away from the wound site into the hydrogel. Bacteria will be contact-killed by the cationic pore walls of the hydrogel. The hydrogel also degrades in the presence of infection-related enzymes, releasing the star cationic PEI into the infection site to contact-kill bacteria there. A second-generation hydrogel was made with the same concept as the first but with simpler crosslinking and possesses more potent effects. This hydrogel was crosslinked by simply mixing the components together in water, which consisted of poly(ethylene glycol) tetra-thiol and poly(ethylene glycol) tetra-maleimide as the hydrogel network, and is tethered with pendant antibacterial polyimidazolium and antioxidative N-acetylcysteine. This hydrogel was able to achieve the same bacterial killing as the first-generation hydrogel, with an even better wound healing on diabetic wounds. Overall, our hydrogels greatly reduce wound bioburden and its associated inflammations, and promote wound healing.